Religious Education Curriculum in the Family: Islamic Perspective - Ahmad Buchori Muslim; Nury Firdausia (STAI Ma'had Aly Al-Hikam Malang, 2021)
This article tries to adapt the concept of religious education curriculum in the family with Islamic perspectives whose main source comes from the thought of Islamic education scholars. Islam considers education in the family to be the oldest informal religious educational institution. The role of parents or families is very important to the successful education of the child, because the child has more time at home with his family. Religious education in the family is intended to shape children into human beings who believe and fear Allah SWT and have noble character and religious values that are carried out in daily life. Seeing how important the role of the family in educating children, a curriculum concept is needed as a reference for Muslim parents in educating their children. Thus, parents can guide their children by providing educational materials that suit the needs, ages, interests, and talents of children, as stated in Ibn Sina and al-Shaibani's thoughts on the concept of education in the family. Besides, aspects of the use of methods in educating children are important things to be considered by parents. Abdullah Nasih Ulwan offered methods that parents can use in educating children, including methods of role models (uswah hasanah), habituation methods, advice (mau’izah) methods, methods of attention, and methods of punishment.